THE EFFECT OF LOCUS OF EXTERNAL INTERNAL CONTROL, FINANCIAL ATTITUDE, POCKET MONEY AND LIFESTYLE ON THE USE OF E-MONEY - Anggari, Alya Nurul; Dewanti, Patriani Wahyu (Universitas Negeri Yogyakarta, 2021)
Abstract: The Effect of Locus of External and Internal Control, Financial Attitude, Pocket Money and Lifestyle on The Use of E-Money. This study aims to determine the influence of Locus of external internal control, financial attitude, pocket money and lifestyle on the use of e-money in accounting students in Yogyakarta. The population is all students of accounting study programs that are still active in 4 universities in Yogyakarta with a total of 200 respondents and 134 is a sample of this research. This study was conducted by questionnaires using multiple liner regression tests. The results showed that the locus of external control and lifestyle positively influenced the locus of internal control, financial attitude and pocket money of students had no effect on the use of e-money in accounting students of the University in Yogyakarta.Keywords: Locus of control external and internal, Financial attitude, Pocket Money, Lifestyle, E- MoneyAbstrak: Pengaruh Locus Of Control Eksternal Dan Internal, Financial Attitude, Uang Saku, Dan Lifestyle Terhadap Penggunaan E-Money. Penelitian ini bertujuan untuk mengetahui pengaruhl Locus of control external dan internal, financial attitude, uang saku dan lifestyle terhadap penggunaan e-money pada mahasiswa akuntansi di Yogyakarta. Populasi dari penelitian ini adalah mahasiswa program studi akuntansi aktif di 4 universitas di Yogyakarta dengan total 200 orang dan 134 merupakan sample penelitian. Penelitian ini dilakukan dengan menyebarkan kuesioner online dengan uji regresi liner berganda. Hasil penelitian menunjukkan locus of control external dan lifestyle berpengaruh positif sedangkan locus of control internal, financial attitude dan uang saku tidak berpengaruh terhadap penggunaan e-money pada mahasiswa akuntansi Universitas di Yogyakarta. Kata Kunci : Locus of control external dan internal, Financial attitude, Uang Saku, Lifestyle, E- Money